Risk Factors for Adverse Events in Patients With Breast, Colorectal, and Lung Cancer. Issue 8 (December 2021) - Weingart, Saul N.; Atoria, Coral L.; Pfister, David; Classen, David; Killen, Aileen; Fortier, Elizabeth; Epstein, Andrew S.; Anderson, Christopher; Lipitz-Snyderman, Allison
Abstract : Objective: The aim of the study was to identify risk factors associated with medical errors and iatrogenic injuries during an initial course of cancer-directed treatment. Methods: In this retrospective cohort study of 400 patients 18 years or older undergoing an initial course of treatment for breast, colorectal, or lung cancer at a comprehensive cancer center, we abstracted patient, disease, and treatment-related variables from the electronic medical record. We examined adverse events (AEs) and preventable AEs by risk factor using the χ 2 or Fisher exact tests. We estimated the association between risk factors and the relative risk of an additional AE or preventable AE in multivariable negative binomial regression models with backwards selection ( P < 0.1). Results: There were 304 AEs affecting 136 patients (34%) and 97 preventable AEs affecting 53 patients (13%). In multivariable analyses, AEs were overrepresented in those with lung cancer compared with patients with breast cancer (incident rate ratio = 1.9, 95% confidence interval = 1.1–3.2). Nonwhite race (1.6, 1.0–2.6), Hispanic or Latino ethnicity (2.0, 0.9–4.1), advanced disease (1.7, 1.1–2.6), use of each additional class of high-risk nonchemotherapy medication (1.6, 1.3–1.9), and chemotherapy (2.1, 1.3–3.3) were all associated with risk of an additional AE. Preventable AEs were associated with lung cancer (7.4, 2.4–23.2), Hispanic or Latino ethnicity (5.5, 1.7–17.9), and high-risk nonchemotherapy medications (1.5, 1.2–2.0). Conclusions: Risk factors for AEs among patients with cancer reflected patients' underlying disease, cancer-directed therapy, and high-risk noncancer medications. The association of AEs with ethnicity merits further research. Risk factor models could be used prospectively to identify patients with cancer at increased risk of harm.